THE PSYCHOSOCIAL CONDITION OF PEOPLE WITH HIV-AIDS IN THE PELITA ILMU FOUNDATION TEBET SOUTH JAKARTA - Alyunzira Wardani; Theresia Martina Marwanti; Ayi Haryani (Indonesian Journal of Social Work, 2018)
The purpose of this research is to obtain empirically the characteristics of the informant, the feeling of people living with HIV when they are infected with HIV-AIDS, thought of people living with HIV when they are infected with HIV-AIDS, behavior or actions of people living with HIV after infection with HIV-AIDS, the physical condition of people living with HIV when they are infected with HIV-AIDS, social relationship PLWHA after being infected with HIV-AIDS, and the expectations of the informant. The method used in this research was qualitative with descriptive research design. The data was collected with interview, observation, and documentation. The informant is determined with purposive sampling, are 5 informants with different HIV-AIDS backgrounds. The reliability used are credibility and confirmability. The technique of data analysis used are data reduction, categorization and data display. The result shows that the psychosocial condition of PLWHA are not good and have problems in their physical condition and social relationship. Informan get the weight loss, get tired easily/lethargic, and have other diseases such as tuberculosis and toxo. Their relationship and social interaction with family and society are not good and distant. Family and society show the refusal attitude, give a stigma, and discrimination to informant. This problem happen because of the lack of acceptance and social support provided by the family to the informants.